If x/y+y/x=-1(x,, yis not 0)find the value of x3-y3
Answers
Answered by
15
According to given sum ,
x/y+y/x=-1
x/y+y/x+1=0
Taking LCM.
![\frac{ {x}^{2} + {y}^{2} + xy }{xy} = 0 \frac{ {x}^{2} + {y}^{2} + xy }{xy} = 0](https://tex.z-dn.net/?f=+%5Cfrac%7B+%7Bx%7D%5E%7B2%7D+%2B+%7By%7D%5E%7B2%7D+%2B+xy+%7D%7Bxy%7D+%3D+0)
![{x}^{2} + {y}^{2} + xy = 0 {x}^{2} + {y}^{2} + xy = 0](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B2%7D+%2B+%7By%7D%5E%7B2%7D+%2B+xy+%3D+0)
By using formula.
![{x}^{3} - {y}^{3} = (x - y)( {x}^{2} + {y}^{2} + xy) {x}^{3} - {y}^{3} = (x - y)( {x}^{2} + {y}^{2} + xy)](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B3%7D+-+%7By%7D%5E%7B3%7D+%3D+%28x+-+y%29%28+%7Bx%7D%5E%7B2%7D+%2B+%7By%7D%5E%7B2%7D+%2B+xy%29)
![{x}^{3} - {y}^{3} = (x - y)(0) {x}^{3} - {y}^{3} = (x - y)(0)](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B3%7D+-+%7By%7D%5E%7B3%7D+%3D+%28x+-+y%29%280%29)
![{x}^{3} - {y}^{3} = 0 {x}^{3} - {y}^{3} = 0](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B3%7D+-+%7By%7D%5E%7B3%7D+%3D+0)
:-)hope it helps u.
x/y+y/x=-1
x/y+y/x+1=0
Taking LCM.
By using formula.
:-)hope it helps u.
jaya1012:
pls mark as brainliest
Similar questions